Development of Convertible Table and Shelf - Kassim, Noraniah (Multidisciplinary Applied Research and Innovation, 2023)
This convertible table and shelf is a multipurpose furniture designed to help the small room owner to save more space by using dual function furniture in a small room. It is one of the developments that helps small room owners to consume a lot of free space after minimising the number of furniture used. This type of problem is common among students and small room or house owners. This furniture may function as both a table and a shelf at the same time, or it can function fully as a shelf or even entirely as a table by transforming using a slider mechanism. It has the features of being portable, user friendly and reduces the space used in a room. It can be placed in a less or equal to 100 ft square size room. Both the table and the shelf can hold a maximum load up to 35 kg based on the stress and strength analysis simulation that had been done using Solidworks software. In the ergonomic aspect, the height of the furniture can be adjusted according to the comfort of theuser when functioning as the table. Moreover, this convertible table and shelf also has an important aspect for safety conscious users which is the safety lock function. The lock system will prevent the furniture from changing or folding from one shape to another. This will be accomplished using fasteners, and it will only be able to convert after the lock feature is gone. This dual function furniture is designed by using SolidWorks software. The physical design is created in accordance with the work sequence, which includes measuring, cutting, drilling, welding, and finishing.